Flavonoids: A Myth or a Reality for Cancer Therapy? - Forni, Cinzia; Rossi, Massimiliano; Borromeo, Ilaria; Feriotto, Giordana; Platamone, Giovambattista; Tabolacci, Claudio; Mischiati, Carlo; Beninati, Simone (Molecules (Basel, Switzerland), 2021)
Nutraceuticals are biologically active molecules present in foods; they can have beneficial effects on health, but they are not available in large enough quantities to perform this function. Plant metabolites, such as polyphenols, are widely diffused in the plant kingdom, where they play fundamental roles in plant development and interactions with the environment. Among these, flavonoids are of particular interest as they have significant effects on human health. In vitro and/or in vivo studies described flavonoids as essential nutrients for preventing several diseases. They display broad and promising bioactivities to fight cancer, inflammation, bacterial infections, as well as to reduce the severity of neurodegenerative and cardiovascular diseases or diabetes. Therefore, it is not surprising that interest in flavonoids has sharply increased in recent years. More than 23,000 scientific publications on flavonoids have described the potential anticancer activity of these natural molecules in the last decade. Studies, in vitro and in vivo, show that flavonoids exhibit anticancer properties, and many epidemiological studies confirm that dietary intake of flavonoids leads to a reduced risk of cancer. This review provides a glimpse of the mechanisms of action of flavonoids on cancer cells.